2021
DOI: 10.3892/mmr.2021.12008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑378d inhibits Glut4 by targeting Rsbn1 in vitamin D deficient ovarian granulosa cells

Abstract: Vitamin D (VD) is not only associated with bone growth and development, but is also closely associated with numerous other pathological conditions. The present study aimed to investigate the effect of microRNA (miRNA/miR)-378d on ovarian granulosa cells by regulating the round spermatid basic protein 1 (Rsbn1) in the absence of VD. The abnormal expression of miRNAs in ovarian tissues of the VD-deficient mouse was analyzed using transcriptome sequencing. miR-378d, glucose transporter 4 (Glut4) and aromatase (Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In this study, a mouse model of VDD was established as previously described (19), and transcriptome sequencing analysis revealed that miR-196b-5p was abnormally downregulated in the ovarian tissues of VD-deficient mice, which was further confirmed using RT-qPCR of the extracted ovarian tissues from the mice. Functional experiments further demonstrated that overexpression of miR-196b-5p mimics facilitated cell proliferation and inhibited apoptosis in KGN cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, a mouse model of VDD was established as previously described (19), and transcriptome sequencing analysis revealed that miR-196b-5p was abnormally downregulated in the ovarian tissues of VD-deficient mice, which was further confirmed using RT-qPCR of the extracted ovarian tissues from the mice. Functional experiments further demonstrated that overexpression of miR-196b-5p mimics facilitated cell proliferation and inhibited apoptosis in KGN cells.…”
Section: Discussionmentioning
confidence: 57%
“…Determination of serum levels of follicle stimulating hormone (FSH), LH, estradiol, and testosterone was performed using commercial ELISA kits (Tongwei Bio, Shanghai, China). Ovarian tissues were collected in 4% formalin for hematoxylin and eosin (H&E) staining or RNAlater (Invitrogen, USA) for RNA sequencing by Genewiz, Inc. (Suzhou, China), as described previously (19).…”
Section: Animal Proceduresmentioning
confidence: 99%
“…Experimental studies have shown that VD can promote follicle development and maturation by regulating oxidative stress and steroid production pathways in the ovarian granulosa cells. [ 36 , 37 ] VD plays an important role in the antiinflammatory, immunosuppressive, antioxidant, and antitissue fibrosis aspects of the body. Therefore, VD may interfere with the pathogenesis of POF by suppressing inflammation, immune response, oxidative stress, and tissue fibrosis to improve POF.…”
Section: Vd Interfere With the Pathological Process Of Pof By Inhibit...mentioning
confidence: 99%